Manhaj Ta’lim Al-Lughah Al-Arabiyyah Min Khilali Al-Kalimat Al Indunisiyyah Dzati Aslin Araby Fi Qamus Al Lughah Al Indunisiyyah - Febri Nur Qomar; Abdul Halim Muhammad (Ukazh: Journal of Arabic Studies, 2020)
اللغة أداة من أدوات الاتصال بين البشر، والتفاهم بين الأفراد. ومن اللغات التي تكلم بها الإنسان هي اللغة العربية. وقد ذكر التاريخ أن الإسلام دخل في إندونيسيا على أيدي العرب الذين جاؤوا من مكة المكرمة. وهذا يعني أنها تتعايش منذ عهد بعيد مع المجتمع الإندونيسي ويؤدي إلى دخول الكلمات العربية في اللغة الإندونيسية (اقتراض اللغة). واستخرج الباحث الكلمات الإندونيسية ذات أصل عربي في قاموس اللغة الإندونيسية الكبير ويرى إمكانية تعليم هذه الكلمات المقترضة للإندونيسيين المبتدئين. معتمدا على المنهج الوصف التحليلي حاول الباحث استخراج هذه الكلمات الإندونيسية ذات أصل عربي في القاموس ثم تحليلها وتقسيمها حسب المعاني بعد دخولها في اللغة الإندونيسية. ثم قام الباحث باستخدام هذه الكلمات لبناء منهج مقترح مقترح لتعليم اللغة العربية. وتول الباحث إلى أن الكلمات الإندونيسية ذا تأصل عربي في قاموس اللغة الإندونيسية الكبير (KBBI) حرف R إلى Z بلغ عددها إلى مائة خمس وخمسين (155) كلمة. وهذه الكلمات تنقسم إلى أربعة أقسام بعد أن دخلت إلى اللغة الإندونيسية؛ منها ما بقيت معانيها في اللغة الإندونيسية، ومنها ما اتسعت معانيها، ومنها ما ضاقت معانيها، ومنها ما انتقلت معانيها. ويمكن بناء منهج تعليم اللغة العربية من خلال هذه الكلمات، وذلك بوضع هذه الكلمات في الحوارات ونصوص القراءة، ثم يأتي دور المدرس لبيان هذه المفردات وينمي مهارات اللغة العربية الأربع وعناصرها الثلاثة من خلال تدريسه. Language is a tool for human communication, and for understanding between individuals. One of the languages ​​in which a person spoke is Arabic. History has mentioned that Islam was introduced to Indonesia at the hands of the Arabs who came from Mecca. This means that it coexists with Indonesian society for a long time and leads to the entry of Arabic words into the Indonesian language (language borrowing). The researcher extracted Indonesian words of Arabic origin in the big Indonesian language dictionary and sees the possibility of teaching these borrowed words to beginners Indonesians. Depending on the approach, the analytical description, the researcher tried to extract these Indonesian words of Arabic origin in the dictionary, then analyze them and divide them according to the meanings after entering into the Indonesian language. Then the researcher used these words to build a suggested curriculum for teaching Arabic. The researcher concluded that the Indonesian words with Arabic origin in the big Indonesian language dictionary (KBBI) letter R to Z numbered one hundred and fifty (155) words. These words are divided into four sections after they entered the Indonesian language, including the meanings of which remained in the Indonesian language, some of which expanded their meanings, some of which narrowed their meanings, and some of them moved their meanings. The method of teaching the Arabic language can be built through these words, by placing these words in dialogues and reading texts, then the teacher comes to explain these vocabulary and develops the skills of the four Arabic language and its three elements through its teaching.